Functions and Mechanisms of Lysine Glutarylation in Eukaryotes - Xie, Longxiang; Xiao, Yafei; Meng, Fucheng; Li, Yongqiang; Shi, Zhenyu; Qian, Keli (Frontiers in Cell and Developmental Biology, 2021)
Lysine glutarylation (Kglu) is a newly discovered post-translational modification (PTM), which is considered to be reversible, dynamic, and conserved in prokaryotes and eukaryotes. Recent developments in the identification of Kglu by mass spectrometry have shown that Kglu is mainly involved in the regulation of chromatin dynamics, oxidative damage, metabolism, and is associated with various diseases. In this review, we firstly summarize the development history of glutarylation, the biochemical processes of glutarylation and deglutarylation. Then we focus on the patho-physiological functions such as glutaric acidemia 1, asthenospermia, etc. Finally, the current computational tools for predicting glutarylation sites are discussed. These emerging findings point to new functions for lysine glutarylation and related enzymes, and also highlight the mechanisms by which glutarylation regulates diverse cellular processes.